The effect of isokinetic and proprioception training on strength, movement and gait parameters after acute supination injury of the ankle ligaments - C. Mucha (AOSIS, 2009)
The effects of a three-week isokinetic training compared to typical proprio -ceptive training on parameters of strength, movement and gait function after acute ankle ligament sprain were investigated. Thirty-nine patients were randomly allocated to two comparison groups. In group 1 (n=20)a proprioceptive training and in group 2 (n=19) an isokinetic strength training (Cybex 6000®) were administered. Thepatients of both groups underwent training five times a week for three weeks. Before and at the end of the treatmentcourse, in both groups isokinetic strength was tested, the range of motion in the ankle joint was recorded and gait wasanalyzed (multicomponent strength measurement platform, Henschel-System®). The maximum isokinetic torque(60°/s) [Nm] and the contact time (monopedal support time) of the injured leg during gait cycle were the basis for evaluation.The data obtained show that in group 2 a significantly greater increase of the maximum isokinetic torque wasattained in almost all range of motion of the ankle joint in the course of treatment. A t the same time, in group 2 theshortening of the contact time in the stance phase of the injured leg could be compensated. The active range of motionin the ankle joint was less at the end of treatment in group 2 than in group 1. The isokinetic training obviously did notonly lead to better strength regeneration, but also to a functionally more stable ankle joint with a rhythmically moreevenly balanced stance phase of the gait cycle.  These results suggest that the used isokinetic training had positive effects on functional stability after acute ankle sprain.